2017
DOI: 10.1177/0003319717706616
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Procoagulant Activity of Microparticles and the Protein Z System in Patients Undergoing Off-Pump Coronary Artery Bypass Surgery

Abstract: To understand the coagulation changes after off-pump coronary artery bypass (OPCAB) surgery, we evaluated the procoagulant activity of microparticles (MPs) and microparticles exposing tissue factor (MPs-TF), together with the levels of total tissue factor (TF), protein Z (PZ), protein Z-dependent protease inhibitor (ZPI), and factor X (FX) before (first day) and 1 week after surgery (seventh day) in plasma samples from 30 patients. Twenty healthy controls were also included. Compared to the controls, patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
6
1
Order By: Relevance
“…Over the past few decades, the mechanisms of acute vascular events of smokers have been well studied, including induction of a hypercoagulable state, increased myocardial work, carbon monoxide-mediated reduction in the oxygen-carrying capacity of the blood, induction of endothelial dysfunction, coronary vasoconstriction, and catecholamine release. [4,16] In the present study, no positive association between smoking and POAF was observed, and smoking may have a protective effect on POAF. With a growing number of related studies, this phenomenon may be explained by that smokers have higher baseline levels of sympathetic activity and higher adrenergic tolerance.…”
Section: Discussioncontrasting
confidence: 73%
“…Over the past few decades, the mechanisms of acute vascular events of smokers have been well studied, including induction of a hypercoagulable state, increased myocardial work, carbon monoxide-mediated reduction in the oxygen-carrying capacity of the blood, induction of endothelial dysfunction, coronary vasoconstriction, and catecholamine release. [4,16] In the present study, no positive association between smoking and POAF was observed, and smoking may have a protective effect on POAF. With a growing number of related studies, this phenomenon may be explained by that smokers have higher baseline levels of sympathetic activity and higher adrenergic tolerance.…”
Section: Discussioncontrasting
confidence: 73%
“…One of the most widely used analytical methods for quantifying MVs levels and markers is flow cytometry (279). There are many different analytical methods used in MVs studies, such as electron microscopy (280), nanoparticle tracking analysis (280), western blot (280), dynamic light scattering (281), and enzyme-linked immunosorbent assay (282), however none of them is currently used in routine diagnostics. The vast majority of methods require special preparation of biological material samples and specialized equipment (283).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, several studies have found that blood microparticle levels are elevated in individuals with CAD [4,5]. Different molecules on the surface of the microparticles mediate procoagulant properties that may lead to an acute coronary event [6].…”
Section: Introductionmentioning
confidence: 99%